A dialogue with the Latin classical tradition in the Argentina of the 19th century: continuities and ruptures (Anclajes, 2016)
Throughout the 19th century, Latin language and culture makes allowed the lettered classes of the River Plate region to legitimize, in a variety of ways, the vernacular experiences and to shape an imaginary republic in the process of forming a nation state. During the first half of the nineteenth-century, the teaching of Latin experience few significant changes in the methodology or textbooks generally used since the pre-independence period. However, in the last third of the nineteenth century, with the creation of the modern system of secondary education, attributed to Bartolome Mitre, new scientific directions in Historical Linguistics were introduced by hired foreign teachers hired to teach, administrate and publish textbooks for specific subjects, among them Latin grammars, conforming to the requirements of technical and scientific progress. In this article, theoretical reflections proceeding from Glotopolitics and from the history of education allow to examine the configuration of national subjectivities and the impact that in this event has had the transmission of “republican virtues” tied to the Latin tradition.
Keywords: Latin; classical tradition; education; Argentina; XIXth century